Knowledge, perception, and attitudes of Universal Health Coverage policies among Alfaisal University students in Saudi Arabia - Mohamad Salim Alkodaymi; Bader Abou Shaar; Nader Ashraf Fawzy; Rola Alhabbbash; Abdulrahman Senjab; Rawan AlSaoud (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND:Saudi Arabia aims to achieve Universal Health Coverage (UHC) by a combination of free public healthcare and mandatory cooperative health insurance. To ensure the effectiveness of UHC policies, every individual should have a strong knowledge of their health-care rights and the system that guarantees it. OBJECTIVES: The aim of this study is to measure the knowledge of Alfaisal students and record their perceptions and attitudes about Saudi Arabia's basic health-care coverage structure and UHC policies. MATERIALS AND METHODS: A cross-sectional survey was developed with 22 items measuring knowledge and 7 items evaluating perception and attitudes and distributed through E-mail with a consecutive sampling method at Alfaisal University to achieve the required calculated sample size for March-April of 2020. The accumulated data were organized, tabulated, and statistically analyzed using SPSS software. Comparison between two groups and more was made using the Chi-square test. RESULTS: Students' self-reported knowledge on the three main knowledge questions ranged from 30.6% to 57.7%, with medical students admitting to similar or worse knowledge compared to their colleagues from other colleges. About 57.3% of our respondents believe the Saudi system provides effective and sufficient healthcare to all, but only 42.7% believe that the system provides financial protection to all. CONCLUSION: The study showed a low level of knowledge about Saudi Arabia's UHC policies among Alfaisal students, especially among medical students, with a generally positive perception and attitudes toward them, although with some serious misconceptions that should be addressed.